# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2-y
\] |
✓ |
✓ |
|
\[
{}\theta ^{\prime } = \frac {9}{10}-\frac {11 \cos \left (\theta \right )}{10}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (y-1\right ) \left (y-3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (y-1\right ) \left (y-3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (y-1\right ) \left (y-3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (y-1\right ) \left (y-3\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\left (y+1\right ) \left (t -2\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{\left (y+2\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t}{y-2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y \left (y-2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y \left (y-2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y \left (y-2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y \left (y-2\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y-12
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y-12
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y-12
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y-12
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (y\right )
\] |
✗ |
✓ |
|
\[
{}w^{\prime } = w \cos \left (w\right )
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = w \cos \left (w\right )
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = w \cos \left (w\right )
\] |
✗ |
✓ |
|
\[
{}w^{\prime } = w \cos \left (w\right )
\] |
✗ |
✓ |
|
\[
{}w^{\prime } = w \cos \left (w\right )
\] |
✗ |
✓ |
|
\[
{}w^{\prime } = \left (1-w\right ) \sin \left (w\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1}{y-2}
\] |
✓ |
✓ |
|
\[
{}v^{\prime } = -v^{2}-2 v-2
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = 3 w^{3}-12 w^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+\cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \ln \left ({| y|}\right )
\] |
✓ |
✓ |
|
\[
{}w^{\prime } = \left (w^{2}-2\right ) \arctan \left (w\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-4 y+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \cos \left (\frac {\pi y}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (\frac {\pi y}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{3}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (\frac {\pi y}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \sin \left (\frac {\pi y}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}-y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -4 y+9 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -4 y+3 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -3 y+4 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y+\sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y-4 \,{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{2}+4 \,{\mathrm e}^{\frac {t}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{\frac {t}{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 3 \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 y = \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 7 \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 3 t^{2}+2 t -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = t^{2}+2 t +1+{\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = t^{3}+\sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-3 y = 2 t -{\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \cos \left (2 t \right )+3 \sin \left (2 t \right )+{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{t}+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {3 y}{t}+t^{5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{t +1}+t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -2 t y+4 \,{\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 t y}{t^{2}+1} = 3
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 y}{t} = t^{3} {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{t +1}+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{t +1}+4 t^{2}+4 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {y}{t}+2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -2 t y+4 \,{\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 y}{t} = 2 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {3 y}{t} = 2 t^{3} {\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (t \right ) y+4
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2} y+4
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{t^{2}}+4 \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+4 \cos \left (t^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -y \,{\mathrm e}^{-t^{2}}+\cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{\sqrt {t^{3}-3}}+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = a t y+4 \,{\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{r} y+4
\] |
✓ |
✓ |
|
\[
{}v^{\prime }+\frac {2 v}{5} = 3 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -2 t y+4 \,{\mathrm e}^{-t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 3 \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2} \left (t^{2}+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\sin \left (y\right )^{5}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\left (t^{2}-4\right ) \left (y+1\right ) {\mathrm e}^{y}}{\left (t -1\right ) \left (3-y\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (y-3\right ) \left (\sin \left (y\right ) \sin \left (t \right )+\cos \left (t \right )+1\right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y+{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3-2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y+{\mathrm e}^{7 t}
\] |
✓ |
✓ |
|